Appeal from the United States District Court for the Eastern District of Arkansas. William Henry Norwood, et al., appellants vs. Everett Tucker, Jr., et al., appellees. March 2, 1961. Before Woodrough, Van Oosterhout, and Matthes, circuit judges (N.pl.)
United States Court of Appeals, for the eighth circuit. No. 16, 586.